Analisis Keterkaitan Perubahan Pola Ruang RTRW Terhadap Izin Usaha Pertambangan di Kecamatan Banawa - Abdul Zidan Hiola; Muhtar Lutfi; Wildani Pingkan S. Hamzens; Rifai; Rita Yunus (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Changes in Regional Spatial Planning (RTRW) policies play an important role in determining the direction of spatial utilization and investment certainty, including in the mining sector. Donggala Regency revised its Regional Spatial Plan through the amendment of Regional Regulation Number 1 of 2012 concerning the Regional Spatial Plan for 2011–2031 into Regional Regulation Number 2 of 2022 concerning the Regional Spatial Plan for 2022–2042. This revision resulted in adjustments to the spatial structure and land-use patterns that potentially influence the development of Mining Business Licenses (IUPs) in Banawa District, one of the regency’s rapidly developing mining areas. This study aims to analyze changes in the RTRW spatial pattern, identify the development of IUPs, and examine the relationship between RTRW spatial pattern changes and IUP development in Banawa District. The research employed a descriptive quantitative approach using spatial overlay analysis and slope analysis methods. Data were collected through observation, interviews, documentation, and literature review. The results indicate that the area designated to accommodate mining activities increased from 228.711 ha to 770.114 ha, representing an addition of 541.403 ha (237%). Correspondingly, the number of IUPs increased from 7 to 17 licenses (142%), while the total IUP area expanded from 168.70 ha to 462.28 ha (174%). The slope analysis revealed a positive relationship between changes in the RTRW spatial pattern and the development of IUPs, indicating that the expansion of mining-designated areas within the RTRW contributed to the increase in both the number and extent of IUPs. However, this increase has not been fully accompanied by improved spatial conformity in land-use utilization.